Zero Emission Guide by The Last Indonesian Minister Regulation of 2022 Uses Blockchain – BIM for Green Efficiency - Priyawan; Husin, Albert Eddy (Rekayasa Sipil, 2024)
As a result of climate change poses a threat and crisis that is currently sweeping the world; one of them is causing drought, rising sea levels, melting polar ice, and heat waves; therefore, the target towards Net Zero Emission (NZE) in 2060 must be an obligation in all countries. Green Building (GB) is a building that meets Building Technical Standards, and It has demonstrated demonstrable success in conserving resources such as water, energy, and other resources. The application of GB principles following the function and classification in every stage of its implementation is expected to reduce greenhouse gas emissions. This research aims to analyze the cost of improvement work based on GB assessment, which is an influencing factor in applying the regulation from the Minister of Public Works and Public Housing (PUPR) Indonesian government. The Technical Guidelines for GB, through the Minister of PUPR No.1 of 2022, is the latest regulation in Indonesia. Blockchain- Building Information Modelling (BIM) and the Implementation of GB using Structural Equation Modelling–Partial Least Square (SEM-PLS) for the analysis. Applying Blockchain-BIM to overcome the cost constraints is proven to increase the cost performance of GB in modern shopping center buildings by 3 - 3.8% in the Basic rating. It is higher when selecting a zero-emission approach for other ratings, dramatically affecting the required green costs.